IMPLEMENTASI PENILAIAN PORTOFOLIO UNTUK MENINGKATKAN KETERAMPILAN MERANCANG PEMBELAJARAN INOVATIF MAHASISWA PGSD UNIRA MALANG - Adzimatnur Muslihasari; Tety Nur Cholifah (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
The research objective was to improve the student skills in designing innovative learning after the portfolio assessment was applied. This type of research was a Classroom Action Research with two cycles carried out in the elementary school learning strategy course for students in semester 3 of PGSD UNIRA Malang in the first semester of the 2018/2019 academic year. The research subjects were 28 students consisting of 5 men and 23 women. The results of the data research were analyzed descriptively. There was improving skills in designing innovative learning that was seen from several indicators, including skills to formulate learning objectives, skills to apply appropriate learning media, skills to select strategies /methods/learning models, skills to describe learning steps, and skills to develop learning evaluation instruments. The results showed an increase in the number of students who had the skills to form learning goals with good and excellent criteria from 8 people in cycle 1 to 24 people in cycle 2. The number of students with the skills to employ learning media with good and excellent criteria increased from 5 people to 23 people. The number of students with the skills to choose a strategy/method/ learning model with good and excellent criteria increased from 5 people to 25 people. The number of students with the skills to describe the steps of learning with good and very good criteria grew from 8 people to 20 people. There were some students with the skills to apply learning media with good and excellent criteria, increasing from 4 to 26 people.